Efektivitas model pembelajaran inkuiri berbantuan augmented reality dalam meningkatkan kemampuan berpikir kritis peserta didik pada pembelajaran matematika kelas v sekolah dasar - Adzkya Salsabila Cahyono; Frida Destini (Didaktika Dwija Indria, 2026)
The problem of low critical thinking skills of students in mathematics learning in fifth grade of elementary school is the main focus of this study. This study aims to describe the effectiveness of the inquiry learning model assisted by Augmented Reality (AR) in improving students' critical thinking skills. This study uses a quantitative approach with an experimental research type, the research design used is a pretest-posttest control group design. The population of this study was all fifth grade students, totaling 40 students. The data collection technique used a descriptive critical thinking ability test instrument and a non-test instrument in the form of an observation sheet. Data analysis was carried out using the N-Gain test. The results of the study indicate that learning with the inquiry model assisted by Augmented Reality (AR) is more effective than learning using the inquiry model without media assistance in improving students' critical thinking skills. This is proven by the N-Gain value obtained by the experimental class of 0.77 (high category) and the control class of 0.63 (medium category), indicating that the application of the Augmented Reality-assisted inquiry learning model is effective in improving students' critical thinking skills in mathematics learning in grade V of SD Negeri 2 Mekarmulya.